2022
DOI: 10.1002/marc.202100854
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Power Photodetectors Based on PVA‐Modified Reduced Graphene Oxide Hybrid Solutions

Abstract: Photodetectors based on reduced graphene oxide (rGO) have attracted much attention owing to their simple and low‐cost fabrication process. However, the aggregation and defects of rGO flakes still limit the performance of rGO photodetectors. Controlling the composition of rGO has become a vital factor for its prospective applications. For example, the interconnection between rGO and polymers for modified morphologies of rGO films leads to an enhanced performance of devices. In this work, a practical approach to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…By modifying the rGO film with hydrophilic polymers, Shih et al 55 demonstrated a feasible method for designing surface homogeneity and improving photodetector performance. The on/off ratio of the PVA/rGO photodetector is 3.5 times higher than that of the rGO photodetector, and the detective improves by 53% even when the photodetector is operated at a low bias of 0.3 V.…”
Section: Graphene-based Photodetectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…By modifying the rGO film with hydrophilic polymers, Shih et al 55 demonstrated a feasible method for designing surface homogeneity and improving photodetector performance. The on/off ratio of the PVA/rGO photodetector is 3.5 times higher than that of the rGO photodetector, and the detective improves by 53% even when the photodetector is operated at a low bias of 0.3 V.…”
Section: Graphene-based Photodetectorsmentioning
confidence: 99%
“…By modifying the rGO film with hydrophilic polymers, Shih et al 55 . demonstrated a feasible method for designing surface homogeneity and improving photodetector performance.…”
Section: Photodetectors Based On Two Dimensional Materialsmentioning
confidence: 99%
“…There have been numerous realizations using graphene, GO or RGO as the active photoactive layer in photodetectors [24][25][26][27][28]. Photodetectors based on RGO have been widely studied recently due to their advantages such as low cost and easy synthesis [29]. Inherently weak optical absorption and the short carrier lifetime of graphene has limited its practical application in photodetectors [30].…”
Section: Introductionmentioning
confidence: 99%
“…The photoresponsivity of the graphene/HfO/Si photodetector is 45.8 A∕W. Moreover, Shih et al 23 demonstrated a practical approach for enhancing surface homogeneity and improving photodetector performance. The PVA/rGO photodetector has an on/off ratio that is 3.5 times higher than that of the rGO photodetector.…”
Section: Introductionmentioning
confidence: 99%
“…The photoresponsivity of the graphene/HfO/Si photodetector is 45.8 A/W. Moreover, Shih et al 23 . demonstrated a practical approach for enhancing surface homogeneity and improving photodetector performance.…”
Section: Introductionmentioning
confidence: 99%